Chronic Non-Communicable Diseases in the International Convention Cuba-Health 2015 - Miguel Ángel Serra Valdés (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
The International Convention Cuba-Health 2015 recently concluded, on April 24 this year. Undoubtedly, it was successful thanks to the quality of the issues discussed in various plenary sessions, workshops, forums and symposiums, and of course, the quality of the papers presented in the different halls. Cuba showed its accomplishments in this regard. A topical issue of vital importance was chronic noncommunicable diseases. Given the challenge they pose, the aspects of the strategies to follow accordingly were devised and discussed. These few lines address the most significant aspects.